Doctor Who? She! Representação e representatividade femininas sob a perspectivas de gênero na narrativa seriada Doctor Who - Silva, Laíne Lopes da (2022)
Of a qualitative nature, this work proposes to analyze a representation and representation of women, focusing on women as the main protagonist of the British series Doctor Who, created in 1963, the oldest science fiction production in history. The series has as its protagonist the character Doctor, a stranger, able to travel in time and with friends, called companions, in its female characters. When close to death, this being can regenerate into another body, a trick that changes of actor, and allows continuity in the series. During the middle of the century, all his regenerations were carried out in male bodies, however, in the year 2017, the first woman in the role of “The Doctor” was announced, a change that generated great repercussion, especially on the internet. Because of this, we seek to answer throughout this questioning the following: how does the representation and representation of women, especially the Doctor, occur in the serial narrative of Doctor Who from the perspective of Cultural and Gender Studies? To this end, we make use of the bricolage of various methods, in which, through a feminine integrative review, we aim to analyze the representation and representativeness in the universe of Doctor Who, with emphasis on the episode The Witchfinders (2018). Thus, the results show that the series intended to fit, even if belatedly, in the current social scenario, in which women achieve more visibility in sociocultural productions and also in science. The Witchfinders highlighted the series' commitment to presenting the story of women. From the integrative review and the physical analysis, we observed that female changes in representations and representations are perceived in the series, but continue in space. Despite having several long characters along the fissure of its existence, the series presents representations in representations and representations, with some advances, but, in general, as discussions and with little depth, they reiterate stereotypes and segregations.